2012
DOI: 10.1519/jsc.0b013e31823f2cd1
|View full text |Cite
|
Sign up to set email alerts
|

Electromyostimulation—A Systematic Review of the Effects of Different Electromyostimulation Methods on Selected Strength Parameters in Trained and Elite Athletes

Abstract: This is the first part of 2 studies that systematically review the current state of research and structure the results of selected electromyostimulation (EMS) studies in a way that makes accurate comparisons possible. This part will focus on the effects of EMS on strength enhancement. On the basis of these results, part 2 will deal with the influence of the training regimen and stimulation parameters on EMS training effectiveness to make recommendations for training control. Out of about 200 studies, 89 trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 56 publications
3
102
0
2
Order By: Relevance
“…Filipovic et al [20] also analysed the NMES effects on chosen endurance parameters in sportspeople. The selection of 89 out of 200 studies was performed in accordance with the following criteria: age (35 years), healthy patient, NMES type (skin stimulation).…”
Section: Discussionmentioning
confidence: 99%
“…Filipovic et al [20] also analysed the NMES effects on chosen endurance parameters in sportspeople. The selection of 89 out of 200 studies was performed in accordance with the following criteria: age (35 years), healthy patient, NMES type (skin stimulation).…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews of studies in healthy subjects have shown MVC force improvements of between 7% and 62% [24,42]. NMES training also was effective in improving muscle strength in patients with advanced disease, such as chronic obstructive pulmonary disease (COPD) and congestive heart failure (CHF), in whom a Cochrane Review found significant improvements in quadriceps muscle strength [43].…”
Section: Chronic Effects Of Nmes Trainingmentioning
confidence: 99%
“…1 Both whole-body EMS of several muscles simultaneously and local EMS applied on single muscle groups have proven to be an effective training modality. 2 A study conducted in elite volleyball players revealed >20% increase in jump height 4 weeks after application of EMS to defined muscles of the lower body. 3 Other studies with EMS applied locally to single muscles have shown positive effects on strength gain.…”
Section: Introductionmentioning
confidence: 99%